The Relationship between Attributional Style and Spiritual Intelligence and Job Performance of Employees of Tabriz University of Medical Sciences - Mina Jasour; Sadegh Maleki Avarsin (Tabriz University of Medical Sciences, 2016)
Background: The aim of this study was to investigate the relationship between attributional style and spiritual intelligence (SI) with job performance of employees of Tabriz University of Medical Sciences in 2015. Methods: The study population consisted of the employees of 8 faculties of Tabriz University of Medical Sciences (n = 647), of which 243 staff members were selected using a stratified sampling method. Data collection was performed using standard Amram Spiritual Intelligence Questionnaire, Paterson Job Performance Questionnaire and Rotter Locus of Control Questionnaire. Data were analyzed using Pearson correlation coefficient and multiple regressions using SPSS. Results: Based on Pearson correlation coefficient, SI was significantly correlated with job performance among the employees. In addition, there was a significant correlation between internal locus of control and job performance; however, external locus of control did not exhibit any correlation with job performance. Furthermore, the results showed a significant relationship between SI components and job performance (P = 0.000). The results of the regression analysis revealed that all the components of SI were predictors of variables for job performance (R2 = 0.26). Conclusion: Considering the tests, it was revealed that there is a positive and meaningful relation between the internal control of attributional style and the elements of the SI with personnel job performance. However, based on the result of the regression with the fixed amount of 26 percent, it seems necessary to pay attention to other effective elements on the performance of personnel, except internal control and elements of SI.